Edukasi Moralitas Anak: Kajian Atas QS. Luqman Ayat 12-19 Perspektif Tafsir Al-Misbah - Khoirul Muthrofin (LPPM STAI Al-Azhar Menganti Gresik, 2023)
Education is a humanizing process. This concept indicates that there is no education if morality is fragile. This article aims to analyze the narrative of surah Luqman verses 12-19, which contains essential themes in moral education for children. Through a literature study, data were obtained by searching written documents based on the text of the commentary of al-Misbah by M. Quraish Shihab. As for data analysis, the researcher used Spradley's notion of componential-taxonomy analysis to make finding meaningful and relevant themes easier. The results of this study found that the concept of moral education in surah Luqman contains content about monotheism, devotion to both parents, and calls for doing various virtues while trying to prevent evil. This study also found that in the text of surah Luqman, there are at least three main points of moral education: spiritual morals, individual morals, and social morals. This research contributes to a more contextual interpretation of educational discourse on children facing social realities in their future lives. At the same time, the concept of amar ma'ruf is education-oriented toward harmony, while nahi munkar is an educational effort oriented towards efforts to avoid communal conflict.